Evaluation of quantitative-qualitative levels of blood pressure by Tensioregulome - Kozyavkina, Nataliya; Popovych, Igor; Vovchyna, Yuliya; Voronych-Semchenko, Nataliya; Zukow, Walery; Popovych, Dariya (Journal of Education, Health and Sport, 2022)
Background. Earlier we showed that the qualitative-quantitative clusters of blood pressure (BP) are very clearly different from each other by age, sex and the constellation of neuro-endocrine, immune and metabolic variables, which we called the Tensioregulome by analogy with the metabolome and the microbiome. The purpose of this study is detailing this concept. Materials and methods. Under an observations were 44 patients with chronic pyelonephritis and cholecystitis in the phase of remission. Testing was performed twice - on admission and after 7-10 days of standard balneotherapy. The main object of the study was BP. We determined parameters of EEG and HRV, plasma levels of adaptation hormones, electrolytes, lipids, and nitrogenous metabolites, components of humoral, cellular, and phagocytic links of immunity and microbiota as well as markers of pyelonephritis. Results. The forward stepwise program identified 42 Tensioregulome parameters as characteristic of quantitative-qualitative blood pressure clusters: 25 EEGs, sympathetic tone, cortisol, calcitonin, Bifidobacteria faeces, 5 metabolic and 5 immune parameters as well as sex and age. The accuracy of patient classification is 97,7%. Another 15 parameters were found to be characteristic, but were outside the discriminant model. Non-linear correlations between the BP and Tensioregulome parameters were revealed. Conclusion. The Tensioregulome allows us to reliably evaluate quantitative-qualitative levels of blood pressure without measuring it with a tonometer.